Avaliação das subpopulações de linfócitos b em pacientes com ataxia-telangiectasia - Silva, Danielli Christinni Bichuete [UNIFESP] (2016)
Intravenous immunoglobulin (IVIG) is increasingly recommended for many diseases apart from primary immunodeficiency diseases (PID). Although effective and safe, adverse reactions may occur. We conducted a 2-year prospective observational study in 117 patients with PID who received regular replacement therapy to examine IVIG’s adverse effects; 1765 infusions were performed (mean = 15/patient) in 75 males and 42 females (aged 3 months to 77 years) in 3 groups: ≤9 years (34.2%), 10–19 years (26.5%), or ≥20 years (39.3%). Fifty patients had common variable immunodeficiency (CVID), 11 had X-linked agammaglobulinaemia (XLA), and 55 had other immune system disorders. The drugs administered were Octagam® (49.1%), Tegeline® (17.3%), Imunoglobulin® (18.6%), Flebogama® (12.9%), Vigam® (1.2%), and Kiovig® (0.4%). Immediate infusion-related adverse reactions occurred in the cases of 38 of 1765 infusions (2.15%, IC95% 1.53%–2.94%), which were classified as mild (81.6%), moderate (10.5%), or severe (7.9%). Time until reaction ranged from 10 to 240 min (mean = 85.7, median = 60). Reaction rates were similar across age groups. The most common reactions were malaise, headache, and abdominal pain. Reported severe events were tightness of the throat and seizure. All symptoms improved with temporary or complete IVIG interruption and symptomatic medications. Sixteen of 38 reactions to infusions occurred in the presence of an acute infection (p = 0.09). Tegeline® represented a greater reaction risk factor than Octagam® (p < 0.001). These results indicate that IVIG infusion can be considered a safe procedure. Low reaction incidence and few severe immediate infusion-related adverse reactions were observed.